73.5k views
1 vote
Find the length of AB with endpoints A(5, 8) and B(-1, 6) Leave answer in simplest radical form.

User Talley
by
4.5k points

1 Answer

5 votes

Answer:

Explanation:

Givens

x2 = 5

x1 = - 1

y2 = 8

y1 = 6

Equation

d = sqrt( (x2 - x1)^2 + (y2 - y1)^2 )

Solution

d = sqrt( (5 - - 1)^2 + (8 - 6)^2 )

d = sqrt( 36 + 4)

d = sqrt(40)

d = 2 * sqrt(10)

User Cleder
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.